2018
DOI: 10.1101/444687
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High throughput droplet single-cell Genotyping of Transcriptomes (GoT) reveals the cell identity dependency of the impact of somatic mutations

Abstract: Defining the transcriptomic identity of clonally related malignant cells is challenging in the absence of cell surface markers that distinguish cancer clones from one another or from admixed non-neoplastic cells. While single-cell methods have been devised to capture both the transcriptome and genotype, these methods are not compatible with droplet-based single-cell transcriptomics, limiting their throughput. To overcome this limitation, we present single-cell Genotyping of Transcriptomes (GoT), which integrat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 75 publications
0
8
1
Order By: Relevance
“…We showed that expression of CALR mutant proteins associated with MPN does not trigger an ER stress. These results were unexpected given that it was recently deduced from transcriptomic data that ER homeostasis was perturbed in CALR variant-expressing MPN [28,29]. However, our data suggest that this UPR pathway activation is not a direct consequence of the expression of CALR mutant proteins.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…We showed that expression of CALR mutant proteins associated with MPN does not trigger an ER stress. These results were unexpected given that it was recently deduced from transcriptomic data that ER homeostasis was perturbed in CALR variant-expressing MPN [28,29]. However, our data suggest that this UPR pathway activation is not a direct consequence of the expression of CALR mutant proteins.…”
Section: Discussioncontrasting
confidence: 75%
“…However, our data suggest that this UPR pathway activation is not a direct consequence of the expression of CALR mutant proteins. On the contrary, it might result from the modification of cell properties, such as an increased proliferation, as suggested by a more predominant activation of the UPR in committed progenitors compared to hematopoietic stem cells (HSC) [29]. Salati et al recently reported a decreased sensitivity toward ER-stress induced apoptosis in cells expressing CALR variants [30].…”
Section: Discussionmentioning
confidence: 99%
“…The recovery of clonotype information together with surface protein marker expression allowed fine separation of specific cell populations of interest, enabling careful determination of molecular phenotypes. Analogous to the use of TCR clonotype information in this study, we have recently used expressed mutations to define and further characterize clonal populations in scRNA-seq data-sets (Genotyping of Transcriptomes, GoT 18 ), an approach that could readily be combined with ECCITE-seq. The method we describe is inherently customizable and we envisage additional oligo-tagged ligands, such as peptide-loaded MHC complexes for detecting specific TCRs, labeled antigens for detection of antigen specific B cells, or antibodies directed against intracellular proteins being added to future iterations of this system.…”
Section: Discussionmentioning
confidence: 99%
“…MutaSeq has distinct advantages and disadvantages compared to other methods for mutational profiling during single-cell RNA-seq currently proposed on preprint servers. GoT-Seq (Nam et al , biorxiv) performs targeted amplifications from cDNA libraries obtained from droplet-based singlecell RNA-seq, and therefore is biased towards mutations near the cDNA 3’ or 5’ end. Moreover, it provides a decreased molecular sensitivity compared to MutaSeq (median 4420 genes detected per CD34+ bone marrow cell, compared to ~2300 in GoT-Seq).…”
Section: Discussionmentioning
confidence: 99%